Default by Land Buyers through Binding Sale and Purchase Agreement with Installments - I Made Arjaya (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Land constitutes a fundamental necessity for society, particularly in Indonesia. Transactions involving land sale and purchase through installment mechanisms are formalized through a Binding Sale and Purchase Agreement PPJB. The implementation of buying and selling land in installments through PPJB occurs with the process of parties coming to the Notary’s office to make PPJB and In PPJB land in installments will be mentioned on the payment deed in several stages and carried out on what date. In the event that sanctions for late payment will be regulated according to the agreement of the parties. This research examines default in such agreements and proposes a typology of total and partial breach to determine proportional legal consequences. Default may occur in different form. Partial breach allows renegotiation, while total breach justifies termination. It is recommended that PPJB agreements explicitly regulate types of breach and legal consequences. Default in PPJB must be analyzed proportionally. The typology proposed provides a more balanced legal framework.